Molecular genomic features associated with in vitro response of the NCI‐60 cancer cell line panel to natural products. Issue 2 (24th November 2020) - Krushkal, Julia; Negi, Simarjeet; Yee, Laura M.; Evans, Jason R.; Grkovic, Tanja; Palmisano, Alida; Fang, Jianwen; Sankaran, Hari; McShane, Lisa M.; Zhao, Yingdong; O'Keefe, Barry R.
Abstract : Natural products remain a significant source of anticancer chemotherapeutics. The search for targeted drugs for cancer treatment includes consideration of natural products, which may provide new opportunities for antitumor cytotoxicity as single agents or in combination therapy. We examined the association of molecular genomic features in the well‐characterized NCI‐60 cancer cell line panel with in vitro response to treatment with 1302 small molecules which included natural products, semisynthetic natural product derivatives, and synthetic compounds based on a natural product pharmacophore from the Developmental Therapeutics Program of the US National Cancer Institute's database. These compounds were obtained from a variety of plant, marine, and microbial species. Molecular information utilized for the analysis included expression measures for 23059 annotated transcripts, lncRNAs, and miRNAs, and data on protein‐changing single nucleotide variants in 211 cancer‐related genes. We found associations of expression of multiple genes including SLFN11, CYP2J2, EPHX1, GPC1, ELF3, and MGMT involved in DNA damage repair, NOTCH family members, ABC and SLC transporters, and both mutations in tyrosine kinases and BRAF V600E with NCI‐60 responses to specific categories of natural products. Hierarchical clustering identified groups of natural products, which correlated with a specific mechanism of action. Specifically, several natural product clusters were associated with SLFN11 gene expression, suggesting that potential action of these compounds may involve DNA damage. The associations between gene expression or genome alterations of functionally relevant genes with the response of cancer cells to natural products provide new information about potential mechanisms of action of these identified clusters of compounds with potentially similar biological effects. This information will assist in future drug discovery and in design of new targeted cancer chemotherapy agents. Abstract : Natural products provide new opportunities for anticancer chemotherapeutics. We examined the associations of molecular features in the NCI‐60 cancer cell lines with response to 1302 plant, marine, and microbial compounds. Expression or mutations in multiple genes were associated with treatment responses, suggesting potential mechanisms of action of natural compounds. This information will assist in future design of new chemotherapy agents.